Faktor Risiko Kematian Pada Pasien Diabetes Melitus dan Penyakit Jantung: Systematic Review - Cindy Muazizah; Hermina Novida (Pusat Riset dan Inovasi Nasional, 2024)
Word Health Organization defines a cause of death as an illness, disease or injury that causes or contributes to death. Diabetes mellitus is a major comorbidity and cardiac arrest is the highest cause of death. Cardiovascular disease is more common in men with an average age of 57 years. There are many types of cardiovascular disease, but the most common and well-known are coronary heart disease and stroke. Basic Health (Riskesdas) in 2018 reported that the incidence of heart and blood vessel disease is increasing from year to year. The main factor in heart disease is uncontrolled blood sugar, while the most common macrovascular complication of diabetes mellitus is coronary heart disease. Causative factors The prevalence of type 2 diabetes mellitus is caused by the interaction between gene susceptibility factors and environmental exposure as follows Genetics and Environment The occurrence of coronary heart disease is closely related to the presence of disorders affecting the blood vessels called atherosclerosis. This research uses a systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). with inclusion and exclusioncriteria, the risk of cardiovascular death and myocardial infarction was higher with increasing values ​​of lysis time and maximum turbidity.